Natural resistance of four Amazon woods submitted to xylophagous fungal infection under laboratory conditions - Reis, Alisson Rodrigo Souza; Reis, Luciane Pereira; Alves Júnior, Miguel; Carvalho, Josiane Celerino de; Silva, Jhonata Ribeiro da (Instituto de Ecología, A.C., 2017)
The present study aimed to assess the natural resistance of four Amazon tropical wood species, used in the production of sawn timber, against infection with xylophagous fungi. Apuleia leiocarpa (amarelão), Dinizia excelsa (angelim vermelho), Vochysia maxima (quaruba), and Bagassa guianensis (tatajuba) were selected to perform the accelerated laboratory test. These species were exposed to white rot xylophagous fungi Pycnoporus sanguineus, Phanerochaete chrysosporium and Schizophyllum commune, and to the brown rot fungus Gloeophyllum abietinum. The laboratory test was performed following the methodology and classification of the natural resistance of wood according to ASTM D2017-86 (American Society for Testing Materials). All species were classified as highly resistant to fungal attack; however, V. maxima lost the highest percentage of weight. Therefore, we recommend that D. excelsa, A. leiocarpa, and B. guianensis be used in the production of sawn timber since they exhibited lower weight loss in the presence of all the fungi tested during a period of 12 weeks.